Factors Influencing the Adoption of Digital Payment Systems Among Millennials in Batu Pahat, Johor - Mohd Nazri, Nur Nasriah; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2026)
Digital payments are becoming more important in Malaysia as people move toward using less cash. Even though millennials are adept with technology, semi-urban areas like Batu Pahat still have low adoption due to system issues, QR code problems, and poor app usability. Therefore, this study is conducted to investigate the factors influencing (performance expectancy, social influence, effort expectancy, perceived security) the adoption of digital payment systems among millennials in Batu Pahat, Johor. This study population consists of 172,800 millennials. Based on the population, the sample needed in this study is 384 respondents of millennials using random sampling. A quantitative method was employed and data were analyzed using SPSS software. Descriptive analysis, reliability analysis, normality test, correlation analysis, and pilot test conducted to achieve the research objective. The results indicate that performance expectancy, social influence, effort expectancy, perceived security examined factors show positive and significant relationships with adoption digital payment systems. The findings provide useful insights to assist policymakers, businesses, and financial institutions in developing strategies to promote wider use of digital payment systems.